Blood group ABO genotyping in paternity testing - Bugert, Peter; Kemp, Katharina; Klüter, Harald (Transfusion medicine and hemotherapy, 2012)
Background: The ABO blood groups result from DNA sequence variations, predominantly single nucleotide and insertion/deletion polymorphisms (SNPs and indels), in the ABO gene encoding a glycosyltransferase. The ABO blood groups A1, A2, B and·predominantly result from the wild type allele A1 and the major gene variants that are characterized by four diallelic markers (261G>del, 802G>A, 803G>C, 1061C>del). Here, we were interested to evaluate the impact of ABO genotyping compared to ABO phenotyping in paternity testing. Methods: The major ABO alleles were determined by PCR amplification with sequence-specific primers (PCR-SSP) in a representative sample of 1,335 blood donors. The genotypes were compared to the ABO blood groups registered in the blood donor files. Then, the ABO phenotypes and genotypes were determined in 95 paternity trio cases that have been investigated by 12 short tandem repeat (STR) markers before. We compared statistical parameters (PL, paternity likelihood; PE, power of exclusion) of both blood grouping approaches. Results: The prevalence of the major ABO alleles and genotypes corresponded to the expected occurrence of ABO blood groups in a Caucasian population. The low resolution genotyping of 4 diallelic markers revealed a correct genotype-phenotype correlation in 1,331 of 1,335 samples (99.7%). In 60 paternity trios with confirmed paternity of the alleged father based on STR analysis both PL and PE of the ABO genotype was significantly higher than of the ABO phenotype. In 12 of 35 exclusion cases (34.3%) the ABO genotype also excluded the alleged father, whereas the ABO phenotype excluded the alleged father only in 7 cases (20%). Conclusion: In paternity testing ABO genotyping is superior to ABO phenotyping with regard to PL and PE, however, ABO genotyping is not sufficient for valid paternity testing. Due to the much lower mutation rate compared to STR markers, blood group SNPs in addition to anonymous SNPs could be considered for future kinship analysis and genetic identity testing.
Gesehen am 08.05.2018